PENGARUH PELATIHAN VIDEO CONTENT CREATOR TERHADAP KOMPETENSI PESERTA PELATIHAN DI WILAYAH KERJA BPSDMP KOMINFO JAKARTA - Mahmudah, Dede; Dewi Hernikawati (Jurnal Studi Komunikasi dan Media, 2024)
Content Creator is considered a profession that can be agile and responsive to adjust and adapt to major changes. The latest skills and knowledge for content creators are important to deal with rapid changes in technology and applications required. This new knowledge can be obtained by participating in training. Therefore, BPSDMP Kominfo Jakarta conducts video content creator training. This study wanted to see if there was a relationship between video content creator training and increased participant competency. The method in this research is a quantitative approach with explanatory research. Respondents in this study were video content creator training participants. As a result, the video content creator training held by BPSDM Kominfo Jakarta increased the competence of the participants in creating video content in online media.